A comparison of two function-based interventions: NCR vs. DRO in preschool classrooms. Issue 3 (3rd July 2018) - LaBrot, Zachary C.; Dufrene, Brad; Pasqua, Jamie; Radley, Keith C.; Olmi, Joe; Bates-Brantley, Kayla; Helbig, Kate; Melendez, Marian; Murphy, Ashley
ABSTRACT: The purpose of this study was to determine the relative efficacy of non-contingent reinforcement (NCR) and differential reinforcement of other behavior (DRO) after behavioral functions were identified through indirect, descriptive, and experimental assessment. Participants included three preschool-age children in three center-based classrooms in a southeastern Head Start agency. Functional behavioral assessment data were used to inform treatment procedures, which were examined with an alternating treatments design. This study examined (a) relative differences in the efficacy of NCR and DRO in decreasing problem behaviors in preschool children, (b) relative differences in the efficacy of NCR and DRO in increasing appropriate behavior, (c) relative preference for functional behavioral assessment procedures, and (d) differential preference for NCR versus DRO for preschool teachers. Results indicated NCR was more effective than DRO for improving behavior for two of three participants, although both NCR and DRO were effective, relative to a control condition, for decreasing problem behaviors and increasing appropriate behaviors.